Structuralism Between Criticism and Ideology - عفيفة, عبير; منذر شباني (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the nature of the transfer of real relations within the language system to these relations in their textual state, meaning that we will review the mechanisms of structural criticism of reality relations in their textual linguistic construction and try to identify how the internal and external linguistic relations appear in the literary text, and this in turn will lead us to what structuralism has done in creating a rupture between the literary components of the text and its real ones, so that structural criticism keeps the text as a basic unit that has its internal relations at the level of the language system without much concern for the real conditions of the text formation, and here the concept of the death of the author emerges.